Thromboembolic events in polycythemia vera - Griesshammer, Martin (Ann Hematol, 2019)
Thromboembolic events and cardiovascular disease are the most prevalent complications in patients with polycythemia vera (PV) compared with other myeloproliferative disorders and are the major cause of morbidity and mortality in this population. Moreover, a vascular complication such as arterial or venous thrombosis often leads to the diagnosis of PV. The highest rates of thrombosis typically occur shortly before or at diagnosis and decrease over time, probably due to the effects of treatment. Important risk factors include age (≥ 60 years old) and a history of thrombosis; elevated hematocrit and leukocytosis are also associated with an increased risk of thrombosis. The goal of therapy is to reduce the risk of thrombosis by controlling hematocrit to < 45%, a target associated with reduced rates of cardiovascular death and major thrombosis. Low-risk patients (< 60 years old with no history of thrombosis) are managed with phlebotomy and low-dose aspirin, whereas high-risk patients (≥ 60 years old and/or with a history of thrombosis) should be treated with cytoreductive agents. Interferon and ruxolitinib are considered second-line therapies for patients who are intolerant of or have an inadequate response to hydroxyurea, which is typically used as first-line therapy. In this review, we discuss factors associated with thrombosis and recent data on current treatments, including anticoagulation, highlighting the need for more controlled studies to determine the most effective cytoreductive therapies for reducing the risk of thrombosis in patients with PV.